Begomoviral Movement Protein Effects in Human and Plant Cells: Towards New Potential Interaction Partners - Krapp, Susanna; Schuy, Christian; Greiner, Eva; Stephan, Irina; Alberter, Barbara; Funk, Christina; Marschall, Manfred; Wege, Christina; Bailer, Susanne M.; Kleinow, Tatjana; Krenz, Bjoern (Viruses, 2017)
Geminiviral single-stranded circular DNA genomes replicate in nuclei so that the progeny DNA has to cross both the nuclear envelope and the plasmodesmata for systemic spread within plant tissues. For intra- and intercellular transport, two proteins are required: a nuclear shuttle protein (NSP) and a movement protein (MP). New characteristics of ectopically produced Abutilon mosaic virus (AbMV) MP (MPAbMV), either authentically expressed or fused to a yellow fluorescent protein or epitope tags, respectively, were determined by localization studies in mammalian cell lines in comparison to plant cells. Wild-type MPAbMVand the distinct MPAbMV: reporter protein fusions appeared as curled threads throughout mammalian cells. Co-staining with cytoskeleton markers for actin, intermediate filaments, or microtubules identified these threads as re-organized microtubules. These were, however, not stabilized by the viral MP, as demonstrated by nocodazole treatment. The MP of a related bipartite New World begomovirus, Cleome leaf crumple virus (ClLCrV), resulted in the same intensified microtubule bundling, whereas that of a nanovirus did not. The C-terminal section of MPAbMV, i.e., the protein's oligomerization domain, was dispensable for the effect. However, MP expression in plant cells did not affect the microtubules network. Since plant epidermal cells are quiescent whilst mammalian cells are proliferating, the replication-associated protein RepAbMVprotein was then co-expressed with MPAbMVto induce cell progression into S-phase, thereby inducing distinct microtubule bundling without MP recruitment to the newly formed threads. Co-immunoprecipitation of MPAbMVin the presence of RepAbMV, followed by mass spectrometry identified potential novel MPAbMV-host interaction partners: the peptidyl-prolyl cis-trans isomerase NIMA-interacting 4 (Pin4) and stomatal cytokinesis defective 2 (SCD2) proteins. Possible roles of these putative interaction partners in the begomoviral life cycle and cytoskeletal association modes are discussed.
EVALuna2:33750

lThe stress granule component G3BP is a novel interaction partner for the nuclear shuttle proteins of the nanovirus pea necrotic yellow dwarf virus and geminivirus abutilon mosaic virus - Krapp, Susanna; Greiner, Eva; Amin, Bushra; Sonnewald, Uwe; Krenz, Björn (Virus Research, 2017)
Stress granules (SGs) are structures within cells that regulate gene expression during stress response, e.g. viral infection. In mammalian cells assembly of SGs is dependent on the Ras-GAP SH3-domain-binding protein (G3BP). The C-terminal domain of the viral nonstructural protein 3 (nsP3) of Semliki Forest virus (SFV) forms a complex with mammalian G3BP and sequesters it into viral RNA replication complexes in a manner that inhibits the formation of SGs. The binding-domain of nsP3 to HsG3BP was mapped to two tandem 'FGDF' repeat motifs close to the C-terminus of the viral proteins. It was speculated that plant viruses employ a similar strategy to inhibit SG function. This study identifies an Arabidopsis thaliana NTF2-RRM domain-containing protein as a G3BP-like protein (AtG3BP), which localizes to plant SGs. Moreover, the nuclear shuttle protein (NSP) of the begomovirus abutilon mosaic virus (AbMV), which harbors a 'FVSF'-motif at its C-terminal end, interacts with the AtG3BP-like protein, as does the TNGSF'motif containing NSP of pea necrotic yellow dwarf virus (PNYDV), a member of the Nanoviridae family. We therefore propose that SG formation upon stress is conserved between mammalian and plant cells and that plant viruses may follow a similar strategy to inhibit plant SG function as it has been shown for their mammalian counterparts. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Stress granules; G3BP; Nuclear shuttle protein; Begomovirus; Abutilon mosaic virus; Nanovirus; Pea necrotic yellow dwarf virus; Bimolecular fluorescence complementation; GFP-trap